KOMPOSISI HASIL TANGKAPAN PANCING ULUR YANG MENGGUNAKAN UMPAN IKAN PARANG-PARANG DAN IKAN TENGGIRI DI PERAIRAN YANG TELAH DIPASANG RUMPON DI PERAIRAN TELUK RHU KABUPATEN BENGKALIS PROVINSI RIAU - Mahyudin '; Pareng Rengi; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in December 2014 in the waters of the Bay Rhu Village District of North Rupat Bengkalis Riau Province. The method used t-test in this study is an experimental method in which data collection was done by direct observation. Oceanographic parameters such ax current max ranged from 20-22 cm / se. The depth range are 26-31 m. T es temperature 28-29oC and Salinity ranges between 30-320/00. The catch with the use of bait fish, mackerel lower and smaller than the use of bait fish machetes, most species of fish caught by using both the feed is Kurau fish and grouper from the above results that the fish caught are demersal fish species which are carnivorous.Keywords : composition, catch, bait.